RANCANG BANGUN APLIKASI REKAPITULASI DATA SISTEM PETUGAS OPERASI JARINGAN (POJ) PLASA TELKOM TAPAKTUAN BERBASIS ANDROID - Razi, Fakhrul (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
The rapid progress the technology is especially in the field of computerized information and technology support a very effective and efficient performance .. Officers operation Network ( POJ ) is the counterpart of from the state telecom who has a duty to run checks and the handling of a disorder in the field.In addition also those POJ make withdrawals cable to the house of customers if there is the installation of new.In operational service the network has officers POJ having a system data storage as data at speedy customers, a cable, data a port and data report.Officers POJ input this kind of data in microsoft office as microsoft word and microsoft exel. The problem is this officer POJ nput in the data using a notebook , while this officer working fix a network of climbing a mast telephone of one mast to the other pole that made the officers had difficulty in me-review data , and also the management of the data still has many because of different file and folder that make the performance of the officers to be slow .In writing this scientific make the application of a recapitulation of the data system the officers network ( POJ ) plasa telkom Tapaktuan based on android.So with mobile phone system is easy to become officers in conducting backup data.Keyword : Information technology, recapitulation POJ, Android-Based